INITIAL ANTIHYPERTENSIVE TREATMENT STRATEGIES AND THERAPEUTIC INERTIA: EVIDENCE FROM A LARGE POPULATION-BASED COHORT. (June 2018) - Rea, F.; Corrao, G.; Merlino, L.; Mancia, G.
Abstract : Objective: In several hypertensive patients, treatment is not upgraded despite lack of blood pressure control, due to therapeutic inertia. Information is limited, however, on the extent of this phenomenon in real-life medicine. The aim of this study was to assess whether two-drug combination as first treatment step results into a reduced role of therapeutic inertia compared to initial monotherapy. Design and method: 125, 635 residents in the Italian Lombardy Region who were aged 40 to 85 years and were newly treated with one antihypertensive drug (n = 100, 982) or two-drug combination therapy (free or fixed dose, n = 24, 653) during 2008 were included in the cohort and followed for 3 years after treatment initiation. The proportion of patients under combination treatment (2 or more drugs) at various time-points during follow-up (6 months, 1, 2 and 3 years) were compared between groups. A log-binomial regression model was used to estimate the prevalence ratio, and its 95% confidence interval (CI), of combination therapy in relation to the initial treatment strategy. Results: In the initial monotherapy group, single drug prescription always remained by far the most common treatment, those prescribed drug combinations being 22%, 27%, 32% and 36% at 6 months 1, 2 and 3 years, respectively. This was in striking contrast with the initial combination treatment group, in which the corresponding percentage of subsequent combination treatment prescriptions were 85%, 82%, 79% and 78%. After adjusting for several covariates, compared to patients under initial monotherapy, those on initial combination therapy showed a markedly greater propensity of being on combination treatment throughout the entire observation period: 3.92 (95% CI, 3.84–4.00) at 6 months, 3.18 (3.12–3.25), 2.56 (2.51–2.60) and 2.23 (2.19–2.27) at 1, 2 and 3 years, respectively (P < 0.001 for all). Conclusions: In our real-life cohort, most patients prescribed initial antihypertensive monotherapy failed to move to combination treatment over the following three years, despite guidelines recommendations. This was largely avoided by the initial prescription of a two-drug combination. Thus, therapeutic inertia plays a major adverse role in uptitration to effective treatment in medical practice.